2019
DOI: 10.1097/01.aog.0000559047.40111.6d
|View full text |Cite
|
Sign up to set email alerts
|

Adherence to New Definitions of Labor Arrest and Failed Induction Decreases Primary Cesareans [16F]

Abstract: INTRODUCTION: To examine the use of cesarean delivery over time for labor arrest and failed induction and identify predictors of meeting criteria for these indications. METHODS: We analyzed rates of primary cesareans due to arrest of dilation, arrest of descent and failed induction among live births at Yale New Haven Hospital from 2010 through 2013. Criteria for labor arrest and failed induction were based on 2012 guidelines, and the proportions of deli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“… 1 , 3 It is possible that the trends demonstrated in this study represent uptake of clinical management recommendations based on contemporary labor data by Zhang et al, 28 which demonstrate slower normal labor progress than the historical standards provided by Friedman. 29 Smaller clinical studies 4 , 6 , 7 , 8 have demonstrated varied findings when longer labor definitions are adopted into clinical management, with some centers demonstrating decreased cesarean deliveries performed for labor arrest and dystocia. Given that trends in decreasing low-risk cesarean deliveries began in 2010, it is possible that physician recognition of increasing population-level labor duration was already beginning to change clinical practice when society guidance was released.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“… 1 , 3 It is possible that the trends demonstrated in this study represent uptake of clinical management recommendations based on contemporary labor data by Zhang et al, 28 which demonstrate slower normal labor progress than the historical standards provided by Friedman. 29 Smaller clinical studies 4 , 6 , 7 , 8 have demonstrated varied findings when longer labor definitions are adopted into clinical management, with some centers demonstrating decreased cesarean deliveries performed for labor arrest and dystocia. Given that trends in decreasing low-risk cesarean deliveries began in 2010, it is possible that physician recognition of increasing population-level labor duration was already beginning to change clinical practice when society guidance was released.…”
Section: Discussionmentioning
confidence: 99%
“…3 The American College of Obstetricians and Gynecologists and Society for Maternal-Fetal Medicine (SMFM) subsequently made specific recommendations for diagnosing labor arrest. 1 Since this guidance, several studies [4][5][6][7][8] have examined trends in cesarean delivery rates and maternal and neonatal outcomes. An analysis 9…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation